Organ-saving and reconstructive plastic surgery of breast cancer - Tamm, Tamara; Vinnуk, Yuri; Starikov, Volodimir; Prokopyuk, Oleksandra; Oleynik, Grіgory; Vlasenko, Vadym (ScienceRise: Medical Science, 2020)
Surgical treatment of breast cancer is an integral part of complex treatment. In recent years, the goal of treatment is not only to ensure long-term relapse-free and metastatic survival, but also a proper quality of life, which requires new approaches to surgery. The aim of the literature review was to analyze current trends in the development of methods of surgical treatment of the breast cancer and ways to improve immediate and late results. The results of the analysis and discussion. Until recently, radical mastectomy was performed to treat breast cancer, which causes long-term lymphovenous complications and significantly impairs the quality of life of patients. In recent decades, there has been a development of breast cancer surgery in the direction of the introduction of organ-saving and reconstructive plastic surgery with the improvement of technology for their implementation. There is no generally accepted concept of the optimal method of surgical treatment, both in terms of the volume of the operation and the choice of the method of reconstruction. Conclusions. The problem of choosing the optimal method of surgical treatment of breast cancer, which should provide oncological radicalism and at the same time a good cosmetic result remains unresolved and requires further research